September 2020 PovcalNet Update : What’s New - Castaneda Aguilar, R. Andres; Fujs, Tony; Jolliffe, Dean; Lakner, Christoph; Gerszon Mahler, Daniel; Nguyen, Minh C.; Schoch, Marta; Vargas Mogollon, David L.; Viveros Mendoza, Martha C.; Baah, Samuel Kofi Tetteh; Yonzan, Nishant; Yoshida, Nobuo (World Bank, Washington, DC, 2020)
The September 2020 update to PovcalNet mainly involves the adoption of the revised 2011 PPPs for the estimation of global poverty. In addition, the coverage rules for reporting regional and global poverty aggregates have been reviewed, resulting in small adjustments. Historical regional and global aggregates are now reported with an annual frequency instead of intervals with varying lengths. Only two surveys have been added and some welfare aggregates have been revised compared with the March 2020 update. National accounts and population input data have been updated. This document explains these changes and the rationale behind them in detail. The data and associated estimates are used for the analysis of global poverty in the forthcoming Poverty and Shared Prosperity Report 2020.